AONT-and-NTRU-based rekeying scheme for encrypted deduplication - Chunfu JIA; Guanxiong HA; Shaoqiang WU; Hang CHEN; Ruiqi LI (Tongxin xuebao)
Rekeying is a good way to protect against key exposure.Most of the existing encrypted deduplication systems are implemented based on message-locked-encryption, in which multiple users with the identical data share the same encryption key.When a user updates keys, that update must be followed by all other data owners, which will incur large computational and communicational overheads.To solve this problem, an AONT-and-NTRU-based rekeying scheme was proposed, a variant of AONT was designed to solve the synchronization problem of multi-user rekeying, and a proxy re-encryption algorithm based on NTRU was introduced to reduce the communicational overhead for the system and computational overhead for clients during rekeying.The efficiency analysis and experimental results show that the proposed scheme has better encryption and decryption efficiency than existing schemes and the time cost of rekeying is significantly reduced.